Aggression in School Children and Adolescents: Its Relationship with Empathy by Spiritual Sensitivity - Janusz Surzykiewicz; Sebastian Binyamin Skalski-Bednarz; Łukasz Kwadrans; Jolanta Muszyńska; Karol Konaszewski (Jagiellonian University Press, 2024)
Background: Aggression is one of the important problems of psychosocial functioning, but it is also an area of physical and mental health among children and adolescents. The purpose of the present study was to examine the role of spiritual sensitivity as a mediator in the relationship between empathy and aggression in a group of school children and adolescents. Participants and procedure: The study included 281 children and adolescents (54% were girls) aged 9-14 years. The study procedure consisted of completing three questionnaires measuring spiritual sensitivity, empathy and aggression. The structural equation modeling using maximum likelihood estimation were used to determine the relationship between variables. Results: Our results suggest that spiritual sensitivity may mediate the relationship between empathy and aggression. Including spiritual sensitivity in the model reduced the negative relationship between the independent and dependent variables, indicating full mediation. Conclusions: In conclusion, the present study has provided some findings suggesting that spiritual sensitivity may indeed be one of the possible mechanisms by which religiosity leads to positive behavioral outcomes. The findings suggest that such internal factors may be important in leveling aggression and that focusing solely on environmental and situational influences may not fully capture individual differences in thinking, emotions and behavior.